The actor speaks voice and the performer - Rodenburg, Patsy 1953-; Dench, Judi (London, uk Bloomsbury Academic, a trademark of Bloomsbury Publishing Plc, 2023)
"Bringing together books and thinkers that have opened up startling new ways of looking at the world, the Bloomsbury Revelations series celebrates the originality and excellence of Bloomsbury's non-fiction publishing. Including books by the likes of Carol J. Adams, Winston Churchill, Slavoj Zizek, Ronald Dworkin, Constantin Stanislavski, Susan Strange and Gilles Deleuze, this is an essential library of the thinkers who have fundamentally shaped the way we see the modern world."
The actor first speaks -- Extending the voice into resonance, range and speech -- Voice and speech meet word and text -- Voice and text meet the rehearsal -- voice, text and rehearsal meet the stage -- The production meets and audience -- Re-creating the work again and again.
Includes index.
Keywords: Acting; Voice culture